User assessment study of Cape Town's historic Company's Gardens : a study to aid its management and improve its recreational opportunities - Young, Michael Howard (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Parks and Recreation) -- University of Stellenbosch, 1991.